2022
DOI: 10.1097/mpg.0000000000003518
|View full text |Cite
|
Sign up to set email alerts
|

Postpyloric Feeding Access in Infants and Children: A State of the Art Review

Abstract: Achieving postpyloric feeding access is a clinical challenge faced by the pediatric gastroenterologist in everyday practice. Currently, there is limited literature published on the topic. This article provides a practical summary of the literature on the different methods utilized to achieve postpyloric feeding access including bedside, fluoroscopic, endoscopic and surgical options. Indications and complications of these methods are discussed as well as a general approach to infants and children that require i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…37 Children who require frequent GJT replacement for dislodgement or equipment issues or who have challenging GJT placement may benefit from consideration of a SJ. 26 There are several limitations related to this consensus paper, including inconsistency with definitions and classifications of JTs in the literature, heterogeneity, and low number of high-quality studies identified on this topic (many retrospective, with small sample sizes and lacking a comparator group). Although a systematic search strategy of multiple databases was undertaken, this study was not a systematic review and studies were included based on relevance and quality.…”
Section: Complications Of Jt Feedingmentioning
confidence: 97%
See 4 more Smart Citations
“…37 Children who require frequent GJT replacement for dislodgement or equipment issues or who have challenging GJT placement may benefit from consideration of a SJ. 26 There are several limitations related to this consensus paper, including inconsistency with definitions and classifications of JTs in the literature, heterogeneity, and low number of high-quality studies identified on this topic (many retrospective, with small sample sizes and lacking a comparator group). Although a systematic search strategy of multiple databases was undertaken, this study was not a systematic review and studies were included based on relevance and quality.…”
Section: Complications Of Jt Feedingmentioning
confidence: 97%
“…DJTs are inserted using either percutaneous placement of a tube from the abdominal wall directly into the proximal jejunum or by bringing a Roux-en-Y loop up from below the duodenojejunal flexure to the skin to form a stoma for catheterization with a feeding tube or button device. [27][28][29] Various insertion methods for jejunal feeding tube placement are described using endoscopic, radiological, and surgical techniques, as well as bedside approaches (for NJT), 26 and combined approaches may be used. nasointestinal tubes should be confirmed by x-ray prior to use for feeding, especially for blind insertion methods.…”
Section: Journal Of Parenteral and Enteral Nutritionmentioning
confidence: 99%
See 3 more Smart Citations